Chalcogen‐Atom‐Annulated Perylene Diimide Trimers for Highly Efficient Nonfullerene Polymer Solar Cells. Issue 23 (15th September 2017) - Duan, Yuwei; Xu, Xiaopeng; Li, Ying; Li, Zuojia; Peng, Qiang
Abstract: This communication reports the synthesis of two novel chalcogen‐atom‐annulated perylene diimide (PDI) trimers with twisted structures, TriPDI‐S and TriPDI‐Se, for efficient nonfullerene polymer solar cells. TriPDI‐Se exhibits more compact molecular arrangement due to the stronger intermolecular interactions induced by the selenium atom. This selenium annulation endows TriPDI‐Se with improved absorption and crystallinity in its blend film. The resulting devices exhibit enhanced J sc of 17.15 mA cm −2 and fill factor (FF) of 66.8%, which are much higher than those of TriPDI‐S devices ( J sc = 16.71 mA cm −2 ; FF = 63.6%). Although TriPDI‐Se exhibits lower‐lying energy levels, TriPDI‐Se devices still obtain a higher V oc of 0.77 V compared to TriPDI‐S devices ( V oc = 0.74 V), which is mainly originated from the reduced recombination in the related devices. Finally, the power conversion efficiency is significantly elevated from 7.86% for TriPDI‐S devices to 8.82% for TriPDI‐Se devices. Abstract : Two novel perylene diimide trimers annulated with different chalcogen atoms, TriPDI‐S and TriPDI‐Se, are synthesized for highly efficient nonfullerene polymer solar cells. TriPDI‐Se devices show a higher power conversion efficiency of 8.82% than that of TriPDI‐S devices (7.86%), which can be attributed to its stronger absorption, higher crystallinity, and larger charge carrier mobility.